Internal derangements of the temporomandibular joint: A review of the anatomy, diagnosis, and management - Andrew L Young (Wolters Kluwer Medknow Publications, 2015)
Internal derangements of the temporomandibular joint are conditions in which the articular disc has become displaced from its original position the condylar head. Relevant anatomic structures and their functional relationships are briefly discussed. The displacement of the disc can result in numerous presentations, with the most common being disc displacement with reduction (with or without intermittent locking), and disc displacement without reduction (with or without limited opening). These are described in this article according to the standardized Diagnostic Criteria for Temporomandibular Disorders, as well as the less common posterior disc displacement. Appropriate management usually ranges from patient education and monitoring to splints, physical therapy, and medications. In rare and select cases, surgery may be necessary. However, in for the majority of internal derangements, the prognosis is good, particularly with conservative care.